The Impact of Forced Marriage in Islamic Law on Divorce Decision Making and Sharia Mechanisms - Muhammadong (Journal of Society and Scientific Studies, 2026)
The purpose of this paper is to analyse forced marriage from the Islamic law perspective, its impact on divorce decisions and sharia mechanisms involved. This study employs a qualitative method with a descriptive design to obtain a comprehensive understanding of the experiences of couples in forced marriages and the regulation of divorce in this context by Islamic law. The research is based on extensive interviews with couples who have been through forced marriage, with specialists in Islamic law and with sharia attorneys. The data analysis was carried out using thematic analysis to discover patterns and topics connected to the psychological repercussions of forced marriage and divorce systems in Islam. The research shows that being coerced into marriage can make the people involved unhappy, stressed and depressed, and typically leads them to decide to get divorced. Islamic divorce methods through talak (husband initiated) and khulu’ (woman initiated) provide a lawful remedy, taking into account rights such as nafkah iddah and property split to ensure fairness. The novelty of this research is the more in-depth exploration of the use of Sharia processes in divorce due to forced marriages. Forced weddings are rarely explored in previous Islamic law studies. The consequences of this study are essential in the context of Islamic law education, especially in providing a fuller awareness of individual rights in marriage and divorce according to sharia. This work can be a reference for future research on similar subjects in the social and legal fields.